Changes in social mixing and attitudes and practices to precautionary measures in a maturing COVID-19 pandemic in six communities in Sudan: a qualitative study - Salma A.E. Ahmed; Rahaf AbuKoura; Abd Elhameed Ahmed; Omama Abdalla; Omnia Kamal Hassan; Ahmed Tom; Ahmed Eldirdiri; Drieg Ismaeil; Israa Zainalabdeen; Nazik Nurelhuda; Aljaile Ahmed; Afrah Abdan; et al. (BMC, 2024)
Abstract Introduction With low COVID-19 vaccination coverage, non-pharmaceutical interventions were critical to mitigating the COVID-19 pandemic in Sudan. We explored changes in social contact patterns, risk perception, attitudes, and practices toward protective measures during an evolving COVID-19 outbreak in six illustrative communities in Sudan. Methods This qualitative study took place in six communities in five Sudanese states using focus group discussions with community members and non-participant structured observations in public spaces between March 2021 and April 2021. A total of 117 participants joined 24 group discussions. We used a two-stage thematic analysis. Results The perceived importance of compliance with individual preventative measures among those who believe in COVID-19 was higher than observed compliance with behaviors in most study sites. Adherence was consistently low and mainly driven by enforced movement restrictions. As restrictions were lifted, social contacts outside the household resumed pre-COVID-19 levels, and risk perception and individual and institutional adherence to protective measures diminished. We identified an environment that is socially and economically unsupportive of preventive practices, compounded by widespread rumours, misinformation, and mistrust in the government-led response. However, we identified new social habits that can contribute to reducing COVID-19 transmission. Conclusion The unfavourable social and economic environment, coupled with the low visibility of the pandemic and pandemic response, has likely modulated the influence of higher risk perception on adopting precautionary behaviours by individuals. Governments and non-governmental actors should increase the visibility of the pandemic and pandemic response, enforce and incentivise infection control measures in public areas, promote emerging preventive social habits, and actively track and address rumours and misinformation related to COVID-19 and COVID-19 vaccines.